The French Revolution and German industrialization: The new institutional economics rewrites history - Michael Kopsidis; Daniel W. Bromley (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2014)
Our purpose here is to challenge the big-bang approach to economic history in which some alleged institutional imposition - a deus machine - is claimed to launch a series of new economic behaviors. This so-called prime mover is then carried forward by the inexorable forces of path dependency to change the course of history. The specific creation story under investigation here is the French Revolution and the subsequent Napoleonic conquest of parts of Germany. We show that recent efforts to re-write German economic history using this theoretical model cannot be supported by the abundant and concerted empirical evidence.
urn:nbn:de:gbv:3:2-29260
Keywords: N43; N53; N63; O43; 330; institutional change; French Revolution; Germany; Prussian reforms; agricultural development; industrialization